Bioecological Parameters of the Black Fig Fly, Silba adipata (Diptera: Lonchaeidae), Collected from Fig Crops in Mexico - Eduardo Paniagua-Jasso; Manuel Alejandro Tejeda-Reyes; Ana Mabel Martínez-Castillo; José Isaac Figueroa-de la Rosa; Diana Vely García-Banderas; Luis Jesús Palma-Castillo; Carlos Patricio Illescas-Riquelme; Samuel Pineda-Guillermo (Insects)
This study assessed several bioecological aspects of the black fig fly, Silba adipata McAlpine (Diptera: Lonchaeidae), the main pest of fig (Ficus carica L.). Figs were collected from eight sites in the Mexican states of Michoacán (Plan de Ayala, Los Tejones, Antúnez, Tangancícuaro, Indaparapeo, El Carrizal, and Charapendo) and Morelos (Telixtac). No infestation was recorded in figs collected in Charapendo, but, in the remaining sites, it was variable (2–33%). Figs from Plan de Ayala and El Carrizal were longer and contained more larvae than those from Telixtac and Los Tejones. Some figs (≤12) collected in Telixtac and Los Tejones contained few pupae or adults. The survival of larval and pupal stages (≤86%) and the proportion of females (40–53%) were determined at the sites where the infestation of figs was >6% (Telixtac, El Carrizal, Plan de Ayala, and Los Tejones). In the second part of this study, the development of individuals collected in Los Tejones was analyzed under constant conditions. The estimated larval duration time was between 13 and 15 d, whereas pupae lasted 11 d. The survival rate and longevity of females and males were very similar. Our results could help design a program for integrated pest management against S. adipata.